2013
DOI: 10.1093/hmg/ddt243
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila TDP-43 dysfunction in glia and muscle cells cause cytological and behavioural phenotypes that characterize ALS and FTLD

Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) are neurodegenerative disorders that are characterized by cytoplasmic aggregates and nuclear clearance of TAR DNA-binding protein 43 (TDP-43). Studies in Drosophila, zebrafish and mouse demonstrate that the neuronal dysfunction of TDP-43 is causally related to disease formation. However, TDP-43 aggregates are also observed in glia and muscle cells, which are equally affected in ALS and FTLD; yet, it is unclear whether glia- or mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 62 publications
(92 reference statements)
9
63
0
1
Order By: Relevance
“…These results showed that most, if not all, neurons expressed hTDP-43, similar to results reported for TBPH expression in the adult CNS [10, 48]. In flies expressing wild type hTDP-43, the majority of the FLAG-TDP-43 signal was located in the nucleus (Fig 4B).…”
Section: Resultssupporting
confidence: 88%
“…These results showed that most, if not all, neurons expressed hTDP-43, similar to results reported for TBPH expression in the adult CNS [10, 48]. In flies expressing wild type hTDP-43, the majority of the FLAG-TDP-43 signal was located in the nucleus (Fig 4B).…”
Section: Resultssupporting
confidence: 88%
“…In recent studies, by our own and collaborating laboratories, both loss and gain of TBPH resulted in highly similar phenotypic and transcriptome alterations (Diaper et al, 2013b;Vanden Broeck et al, 2013). A consistent observation throughout these and other reports was that TBPH dysfunction, caused by either increased or decreased levels of TBPH, results in neuronal loss (Diaper et al, 2013a(Diaper et al, , 2013bFeiguin et al, 2009;Lin et al, 2011;Ritson et al, 2010;Vanden Broeck et al, 2013;Wang et al, 2011). In addition, our work suggested that both conditions lead to a specific microtubule-based disruption of ecdysteroid receptor-mediated gene program switching at the pupal to adult transition resulting in apoptosis of bursicon neurons and early adult maturation and wing expansion defects (Vanden Broeck et al, 2013).…”
Section: Introductionsupporting
confidence: 70%
“…Expression of wild-type human TDP-43 causes retinal degeneration, neuronal death, and axonal loss (Choksi et al, 2014;Estes et al, 2011;Hanson et al, 2010;Li et al, 2010;Miguel et al, 2011;Ritson et al, 2010). A consistent observation is that the severity of wild-type TDP-43 toxicity is strongly dependent on its expression levels (Diaper et al, 2013a(Diaper et al, , 2013bEstes et al, 2011;Feiguin et al, 2009;Gregory et al, 2012;Li et al, 2010Li et al, , 2013bLu et al, 2009;Ritson et al, 2010;Voigt et al, 2010) and RNA-binding properties (Ihara et al, 2013;Voigt et al, 2010). However, when comparing wild-type and ALS-associated TDP-43 mutants results have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in transgene expression level and differences in the nature of the mutation and species being studied almost certainly underlie the discrepancies in these studies, and make comparison difficult. In addition, a recent study reported that muscle specific knockdown or overexpression of the Drosophila TDP-43 orthologue TBPH, causes motor abnormalities versus motor deficits with early lethality respectively (Diaper et al, 2013). The authors suggested that changes in the Drosophila orthologues for EAAT1/EAAT2 which are involved in glutamate transport, might underlie the phenotype in both knockdown as well as overexpression models.…”
Section: Glial Cells Contribute To Motor Neuron Degenerationmentioning
confidence: 99%